Redenomination Policy and Economic Performance: Experimental and Historical Approach - Falikhakh Nur Baeti; Bambang Juanda; Alla Asmara (Signifikan: Jurnal Ilmu Ekonomi, 2018)
The discourse of redenomination policy has existed since 2010. This research analyzes impact of economic growth, type of goods, transitions period and redenomination stages towards economic performance which measured from the change in the price of transactions and the number of transactions. This research used primary data and secondary data; the primary data was collected through experimental economy. The percentage of the change in price of transactions after redenomination in low economic growth condition showed an increase, while in high economic growth condition showed a decrease. Secondary data was gathered to analyze the deciding factor in the success of redenomination through logistic analysis method. The result showed that the variable of economic growth, unemployment rate and the level of democratization in a country affect the success of the implementation of redenominationDOI:10.15408/sjie.v7i2.6568